1983
DOI: 10.3758/bf03326765
|View full text |Cite
|
Sign up to set email alerts
|

Central neural influences on the human retina during selective attention

Abstract: Two controversial issues were investigated. One concerned the question of whether cen· trifugal fibers project to the human retina, and the other, the question of whether precortical fil· ters which differentially transmit relevant and irrelevant information during selective attention exist. The issues were addressed jointly by studying the effects of selective attention on evoked responses obtained from the retina and over the occipital cortex. Selective attention was manipulated by requiring subjects to resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…It is obvious that the changes of this activity in relation to the phases of the behavior can be accomplished only by efferent influences on the retina. At present, much data has accumulated demonstrating the existence of efferent fibers in the optic tract and of efferent influences on the retina in different species ranging from frogs to man (e.g., Hasselt, 1972;Livingston, 1978;Eason, Oakley, &Flowers, 1983) and including rabbits (Cragg, 1962). However, the significance of these influences was usually either considered unclear or explained as modulation of peripheral sensory elements' responses to the stimuli of the specific modality, related, for example, to intermodal interaction (Granit, 1955;Santini, 1976;Witkovsky, 1971).…”
Section: Behaviorally Related Activations Of Peripheral Neuronsmentioning
confidence: 99%
“…It is obvious that the changes of this activity in relation to the phases of the behavior can be accomplished only by efferent influences on the retina. At present, much data has accumulated demonstrating the existence of efferent fibers in the optic tract and of efferent influences on the retina in different species ranging from frogs to man (e.g., Hasselt, 1972;Livingston, 1978;Eason, Oakley, &Flowers, 1983) and including rabbits (Cragg, 1962). However, the significance of these influences was usually either considered unclear or explained as modulation of peripheral sensory elements' responses to the stimuli of the specific modality, related, for example, to intermodal interaction (Granit, 1955;Santini, 1976;Witkovsky, 1971).…”
Section: Behaviorally Related Activations Of Peripheral Neuronsmentioning
confidence: 99%
“…It has been hypothesized that the early ERP attention effects, such as the PI amplitude modulation, may reflect processing in the visual cortex, subcortical structures, or even in the retina itself (e.g., Eason, 1981;Eason, Oakley, & Flowers, 1983;Harter & Aine, 1984;Van Voorhis & Hillyard, 1977). However, little direct evidence exists that links these attention-sensitive ERPs to specific brain structures.…”
Section: Attention Kffectsmentioning
confidence: 99%
“…attention to visual stimuli, these effects comprise a modulation of the early occipital P1 and N1 waveforms for relevant stimuli, contralateral to the location of the stimulus, an effect that is known as "Sensory Gain"~Eason, 1981;Eason, Harter, & White, 1969;Eason, Oakley, & Flowers, 1983;Harter, Aine, & Schroeder, 1982;Hillyard, Simpson, Woods, Van Voorhis, & Münte, 1984;Luck & Hillyard, 1994;Mangun & Hillyard, 1988;Neville & Lawson, 1987;Rugg, Milner, Lines, & Phalp, 1987!. The effects of spatial attention following early P1 and N1 modulations are less consistent, however. Some studies have reported modulations of occipital P2 and N2 waves, and sometimes the P3 component~Eason et al, 1969P3 component~Eason et al, , 1983Mangun & Hillyard, 1988!.…”
mentioning
confidence: 99%